Extremely Low Frequency Electromagnetic Field (ELF-EMF) and childhood leukemia near transmission lines: a review - P. A. Kokate; A. K. Mishra; S. K. Lokhande; G. L. Bodhe (Advanced Electromagnetics, 2016)
This article presents a systematic review of most cited studies from developed countries those shed light on the potential relation between childhood leukemia and extremely low frequency electromagnetic field (ELF-EMF). All the findings of articles critically segregated as per some neglected parameters like number of samples, exposure duration, frequency range, distance from the radiation sources, and location during measurement of magnetic field density near power lines. Literature of major 50 studies are divided according to pooled analysis / meta-analysis, residential zone assessment and case-control studies.